Evaluasi Program Badan Usaha Milik Desa Dalam Pemberdayaan Masyarakat Di Desa Sidodadi Kecamatan Langsa Lama Pemerintahan Kota Langsa - Laras Adelia Iskandar; Tunggul Sihombing (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study aims to find out and describe how the results and impacts of the implementation of the Village Owned Enterprise Program (BUMDes) have been running in Sidodadi Village, Langsa City.The research method used is a descriptive research method with a qualitative approach. Data collection techniques were carried out by means of interviews, observation and documentation. The results of this study indicate that the Village Owned Enterprises (BUMDes) program in Sidodadi Village, Langsa City is not yet fully optimal for increasing income and empowering the government and the community to need new policies to increase village income. The government's effectiveness indicators welcome suggestions from the public. In the efficiency indicators, the community is very helpful and feels involved in the process. In the indicator of the adequacy of the value empowerment program, it plays a good role in helping the community's economy. In the indicator of equity, the community assesses that the decisions taken by the bumdes are fair enough. On the indicators of responsiveness, the clarity of the program made by bumdes is very good. On the indicators of the accuracy of the empowerment program in the village of Sidodadi, it has been going well, but it must be bolder to develop the potential of the village.